Global diffusion of protest riding the protest wave in the neoliberal crisis - Della Porta, Donatella 1956-; Della Porta, Donatella 1956- (Routledge, 2025)
1. Riding the wave: Protest cascades, and what we can learn from them / Donatella della Porta -- 2. The spirit of Gezi: A relational approach to eventful protest and its challenges / Donatella della Porta and Kivanc Atak -- 3. Brazil's popular awakening -- June 2013: Accounting for the onset of a new cycle of contention / Mariana S. Mendes -- 4. Making sense of "La Salida": Challenging left-wing control in Venezuela / Juan Masullo -- 5. The Marikana Massacre and Labor Protest in South Africa / Francis O'Connor -- 6. Left in translation: The curious absence of austerity frames in the 2013 Bulgarian protests / Julia Rone -- 7. "Sow hunger, reap anger": From neoliberal privatization to new collective identities In Bosnia-Herzegovina / Chiara Milan -- 8. A spirit of Maidan?: Contentious escalation in Ukraine / Daniel P. Ritter -- 9. Riding the wave: Some conclusions / Donatella della Porta.
Keywords: Protest movements -- History -- 21st century.; Protest movements -- Cross-cultural studies.; Neoliberalism